Non‐adherence to heart failure medications predicts clinical outcomes: assessment in a single spot urine sample by liquid chromatography‐tandem mass spectrometry (results of a prospective multicentre study). (3rd May 2021) - Gupta, Pankaj; Voors, Adriaan A.; Patel, Prashanth; Lane, Dan; Anker, Stefan D.; Cleland, John G.F.; Dickstein, Kenneth; Filippatos, Gerasimos; Lang, Chim C.; van Veldhuisen, Dirk J.; Metra, Marco; Zannad, Faiez; et al.
Abstract: Aims: Liquid chromatography‐mass spectrometry (LC‐MS/MS) is an objective new technique to assess non‐adherence to medications. We used this method to study the prevalence, predictors and outcomes of non‐adherence in patients with heart failure with reduced left ventricular ejection fraction (HFrEF). Methods and results: This study included 1296 patients with HFrEF from BIOSTAT‐CHF, a study that aimed to optimise guideline‐recommended therapies. Angiotensin‐converting enzyme inhibitors (ACEi), angiotensin receptor blockers (ARBs), mineralocorticoid receptor antagonists, β‐blockers and loop diuretics were measured in a single spot urine sample at 9 months using LC‐MS/MS. The relationship between medication non‐adherence and the composite endpoint of all‐cause death or heart failure hospitalisation, over a median follow‐up of 21 months, was evaluated. Non‐adherence to at least one prescribed medication was observed in 45.9% of patients. The strongest predictor of non‐adherence was non‐adherence to any of the other medication classes ( P  < 0.0005). Regional differences within Europe were observed. On multivariable analyses, non‐adherence to ACEi/ARBs and β‐blockers was associated with an increased risk of the composite endpoint [hazard ratio (HR) 1.38, 95% confidence interval (CI) 1.09–1.95, P  = 0.008 and HR 1.48, 95% CI 1.12–1.96, P  = 0.006, respectively). Non‐adherence to β‐blockers was also associated with an increased risk of death (HR 2.48, 95% CI 1.67–3.68, P  < 0.0005). Patients who were non‐adherent to loop diuretics were healthier and had a decreased risk of the composite endpoint (HR 0.69, 95% CI 0.51–0.93, P  = 0.014). Non‐adherence to mineralocorticoid receptor antagonists was not related to any clinical outcome. Conclusion: Non‐adherence to medications, assessed by a single urine test, is common and predicts clinical outcomes in patients with HFrEF.